2021
DOI: 10.1007/s00405-021-07187-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rapid maxillary expansion on hearing loss and otitis media in cleft palate children

Abstract: Purpose Otitis media with effusion (OME), recurrent acute otitis media and conductive hearing loss (CHL) are significantly prevalent in children with cleft palate (CP) and cleft lip and palate (CLP). Rapid Maxillary Expansion (RME) appears to have a positive effect also on middle ear disorders in these patients. The study aims to offer a prospective evaluation of RME effects in a group of patients with CP/CLP in terms of OME, CHL. Methods A prospective observational study was conducted. Thirty-four CP, CLP and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Also, ETA proved beneficial in causing significant improvement in patients having combined cleft lip and palate [54]. These children's conductive hearing loss and middle ear effusion improved significantly during RME and after six months of follow-up [55]. Also, a study showed that the correction of the palatal anatomy through RME had a positive and statistically significant effect on improving hearing and middle ear function in patients without cleft and with bilateral cleft lip and palate, with normal hearing levels and with mild conductive hearing loss.…”
Section: Other Syndromesmentioning
confidence: 99%
“…Also, ETA proved beneficial in causing significant improvement in patients having combined cleft lip and palate [54]. These children's conductive hearing loss and middle ear effusion improved significantly during RME and after six months of follow-up [55]. Also, a study showed that the correction of the palatal anatomy through RME had a positive and statistically significant effect on improving hearing and middle ear function in patients without cleft and with bilateral cleft lip and palate, with normal hearing levels and with mild conductive hearing loss.…”
Section: Other Syndromesmentioning
confidence: 99%